Development of a New Self-Centring Structural Connector for Seismic Protection of Structures. (February 2022) - Mohammadi Darani, Farhad; Zarnani, Pouyan; Quenneville, Pierre
Abstract: The concept of seismically low-damage structures was introduced by researchers to decrease the likelihood of irreparable damage as well improving the response of the structure. The need to shift from conventional ductile design to a less ductility (damage) oriented design was emphasised by different researchers in New Zealand and across the world back in the 1990s and 2000s. Damage Avoidance Design (DAD) philosophy introduced in the early 2000s took the idea of low-damage design to another level. Self-centring is the main aspect of a DAD designed. However, the need to change the seismic design philosophy was mostly felt by the community and decisions makers after the considerable financial and social loss resulted from the 2011 Christchurch earthquake. Several damage-avoidance concepts and solutions have been introduced and developed in the past. However, most of these solutions haven't been widely implemented in practice because of the complexity and extra construction costs. This research aims to overcome this gap by introducing a new solution that can be easily adopted by the construction industry without imposing extra complexity and construction costs. This paper presents the development of a new innovative seismic device named as Self-Centring Structural Connector (SSC) as a new self-centring friction damping device. The main purpose of this device is to provide a cost-efficient yet flexible solution to achieve a range of efficient DAD structures in practice. In this paper, the principles of the force-deflection relationship for the SSC is analytically developed and validated through experimental investigation. In addition, the influence of various parameters affecting joint performance are studied through an analytical model. Finally, some possible applications of this device are introduced. As per the findings based on the analytical modelling and experimental investigation, it can be observed that the joint performs well to achieve the design and construction objectives making it a suitable solution for DAD.